RUN Algorithm Based 2D-PIDF-(1+PIDDFF) Controller for Load Frequency Control in a Microgrid - Patel, Shweta; Sahoo, Bibhuti Prasad; Nayak, Anup Abhijeet; Raj, Mayank (2021 3rd International Conference on Advances in Computing, Communication Control and Networking (ICAC3N), 2021)
This study presents the optimal design of a 2D-PIDF-(1+PIDDFF) controller using the RUN algorithm for control of the frequency of a multi-micro grid. For tuning the parameters of the controller, Integral of Time multiplied Absolute Error (ITAE) is considered here as the objective function. Considering various distributed energy resources (DERs), renewable energy sources (RES), and energy storage systems, a multi-microgrid model is designed. A recently published RUN algorithm utilizing the Runge Kutta method is applied for tuning parameters of controllers. Two-degree of freedom PID with derivative filter cascaded with PI with double derivative & derivative filters named as 2D-PIDF-(1+PIDDFF) is proposed here as frequency controller. The efficacy of the proposed RUN tuned 2D-PIDF-(1+PIDDFF) controller for frequency regulation is compared over other RUN tuned PIDF, 1+PIDDFF, PIDF-(1+PIDDFF), and CMVO tuned PID and FPIDF-OM. Out of these controllers, minimum ITAE is obtained by RUN tuned 2D-PIDF-(1+PIDDFF) controller with an improved dynamic response, which shows its usefulness.